2003
DOI: 10.1038/ncb1047
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CFTR in uterine bicarbonate secretion and the fertilizing capacity of sperm

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP-activated chloride channel expressed in a wide variety of epithelial cells, mutations of which are responsible for the hallmark defective chloride secretion observed in cystic fibrosis (CF). Although CFTR has been implicated in bicarbonate secretion, its ability to directly mediate bicarbonate secretion of any physiological significance has not been shown. We demonstrate here that endometrial epithelial cells possess a CFTR-mediated bicarbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 22 publications
3
80
0
2
Order By: Relevance
“…This is consistent with the results obtained in earlier studies using spermatozoa from various species [Lee and Storey 1986;Shi and Roldan 1995a;Visconti et al 1995;. Our previous studies have demonstrated that the involvement of CFTR in uterine bicarbonate secretion and the fertilizing capacity of sperm were important [Wang et al 2003]. Previously, some studies proposed that a crucial role of the CFTR is to conduct both Cl À and HCO 3 À [Poulsen et al 1994;Reddy and Quinton 2001].…”
supporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with the results obtained in earlier studies using spermatozoa from various species [Lee and Storey 1986;Shi and Roldan 1995a;Visconti et al 1995;. Our previous studies have demonstrated that the involvement of CFTR in uterine bicarbonate secretion and the fertilizing capacity of sperm were important [Wang et al 2003]. Previously, some studies proposed that a crucial role of the CFTR is to conduct both Cl À and HCO 3 À [Poulsen et al 1994;Reddy and Quinton 2001].…”
supporting
confidence: 82%
“…This has been considered to be indicative of the completion of capacitation [Florman and Babcock 1991;Jaiswal and Eisenbach 2002;Visconti et al, 1998;Yanagimachi 1994]. Therefore, the sum of ''B þ AR'' patterns of spermatozoa during incubation that undergo capacitation is generally taken as an indicator for completion of capacitation [Barboni et al 1995;DasGupta et al 1994;Visconti et al 1998;Wang et al 2003;Xu et al 2007]. Although there was no significant difference (P 4 0.05) observed in the B pattern between GABAtreated ( Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of capacitation factors (such as HCO 3 -) and decapacitation factors [1,2] have been implicated in these processes. Although the presence of decapacitation factors in the seminal plasma has been reported, no such factor intrinsic to the sperm has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian spermatozoa cannot undergo fertilization without proper activation, termed 'capacitation', in the female tract [1]. During capacitation, extensive changes occur in various sperm compartments.…”
Section: Introductionmentioning
confidence: 99%